Child-Friendly Justice – Slovenian Perspective - Burkelc Juras, Lina (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The article presents the position, rights, and participation possibilities of children in different civil and criminal proceedings in Slovenia. It introduces the constitutional framework for the protection of children’s rights and some fundamental guarantees for children in all types of proceedings. It provides a systematic overlook of the fundamental legislation dealing with children’s rights in civil litigation, non-contentious civil proceedings, administrative proceedings, and criminal proceedings. Furthermore, it highlights some key findings from all these different types of proceedings involving the principle of the best interest of the child and the child’s right to express their opinion, as well as certain procedural adaptations that were made to accommodate children’s interests and their specific position throughout the relevant legislation in different fields of law. Through examination of the relevant provisions, it concludes that progress has been made, particularly with the unification of family law proceedings with the relatively new Family Code and Non-Contention Civil Procedure Act; however, further harmonisation is still needed, especially in criminal cases involving minors. Overall, Slovenia’s legal system demonstrates a commitment to prioritising children’s participation, representation, and best interests and sufficiently protects children’s rights in various civil and criminal proceedings. Keywords: protection of children’s rights, children’s participation, civil proceedings, criminal proceedings, administrative proceedings, best interests of the child, the right to express opinion